A pragmatic approach for integrating molecular tools into biodiversity conservation - Bertola, Laura (2024)
Molecular tools are increasingly applied for assessing and monitoring biodiversity and informing conservation action. While recent developments in genetic and genomic methods provide greater sensitivity in analysis and the capacity to address new questions, they are not equally available to all practitioners: There is considerable bias across institutions and countries in access to technologies, funding, and training. Consequently, in many cases, more accessible traditional genetic data (e.g., microsatellites) are still utilized for making conservation decisions. Conservation approaches need to be pragmatic by tackling clearly defined management questions and using the most appropriate methods available, while maximizing the use of limited resources. Here we present some key questions to consider when applying the molecular toolbox for accessible and actionable conservation management. Finally, we highlight a number of important steps to be addressed in a collaborative way, which can facilitate the broad integration of molecular data into conservation.